INTEGRATED MARKETING COMMUNICATION STRATEGY FOR SME (SMALL AND MEDIUM ENTERPRISES) OF TRADITIONAL HERBAL AND BEVERAGES - Rani Sukma Ayu Suteja; Liestianingsih Dwi Dayanti; Angga Prawadika Aji; Santi Isnaini; Yayan Sakti Suryandaru; Titik Puji Rahayu; Andria Saptyasari; Irfan Wahyudi; Ratih Puspa; Nurul Ratna Sari; Dina Septiani; Nisa Kurnia Illahiati (Darmabakti Cendekia: Journal of Community Service and Engagements, 2021)
Background: This program begins with observation on SME of traditional herbal and beverages in Kampung Genteng Candirejo Surabaya. Early observation shows difficulties faced by SME to market their products. Objective: This program is expected to provide information and education about marketing communication strategies for SME of traditional herbal and beverages in Kampung Herbal Candirejo Surabaya. Method: Early observation is to find problems, conducting seminar and workshop, and also evaluating community empowerment. Results: Audiences understand about the impotances of marketing communication and innovation. They also improve their skills in using integrated marketing communication to sell their products to customers. Conclusion: This community service program has achieved its goals.